A molecular probe for detecting cholinesterase activity in MRI - Sajal Sen; Miranda Dawson; Gregory D. Thiabaud; Kyle Backman; Itay Fayer; Sayani Das; Eliza Whitmire; Catherine Kung; Ali Barandov; Alan Jasanoff (Proceedings of the National Academy of Sciences, 2025)
Cholinesterase (ChE) enzymes terminate action of the neurotransmitter acetylcholine at synapses and neuromuscular junctions throughout the body. Noninvasive strategies for monitoring these enzymes could be important for studying basic biology of cholinergic systems and disorders that affect their function. To address this goal, we developed an imaging probe that allows activity of ChE to be detected using MRI. The probe, called ChERT, undergoes enzymatic processing that reduces its solubility, promoting accumulation near sites of cholinesterase activity. Following wide-field brain delivery, ChERT produces MRI contrast changes in brain regions known to be enriched in cholinesterases; these are suppressed in the presence of a selective enzymatic inhibitor, confirming their specificity. After abdominal delivery, ChERT labels regions of the gut where ChE expression is expected. In both the brain and periphery, colocalization of ChERT with ChE could be confirmed and visualized at higher resolution by fluorescence microscopy, owing to optical properties of the probe architecture. The ChERT agent thus provides a potentially versatile basis for assessment of cholinergic phenotypes throughout the body.